Differential regulation of extracellular tissue inhibitor of metalloproteinases-3 levels by cell membrane-bound and shed low density lipoprotein receptor-related protein 1. - Scilabra, S; Troeberg, L; Yamamoto, K; Emonard, H; Thøgersen, I; Enghild, J; Strickland, D; Nagase, H (2013)
Tissue inhibitor of metalloproteinases-3 (TIMP-3) plays a key role in regulating extracellular matrix turnover by inhibiting matrix metalloproteinases (MMPs), adamalysins (ADAMs), and adamalysins with thrombospondin motifs (ADAMTSs). We demonstrate that levels of this physiologically important inhibitor can be regulated post-translationally by endocytosis. TIMP-3 was endocytosed and degraded by a number of cell types including chondrocytes, fibroblasts, and monocytes, and we found that the endocytic receptor low density lipoprotein receptor-related protein-1 (LRP-1) plays a major role in TIMP-3 internalization. However, the cellular uptake of TIMP-3 significantly slowed down after 10 h due to shedding of LRP-1 from the cell surface and formation of soluble LRP-1 (sLRP-1)-TIMP-3 complexes. Addition of TIMP-3 to HTB94 human chondrosarcoma cells increased the release of sLRP-1 fragments of 500, 215, 160, and 110 kDa into the medium in a concentration-dependent manner, and all of these fragments were able to bind to TIMP-3. TIMP-3 bound to sLRP-1, which was resistant to endocytosis, retained its inhibitory activity against metalloproteinases. Extracellular levels of sLRP-1 can thus increase the half-life of TIMP-3 in the extracellular space, controlling the bioavailability of TIMP-3 to inhibit metalloproteinases.